Formulation and Evaluation Testing of Cream Nail Polish from Impatiens balsamina L. Seed Powder - Sahra, Baiq Yatmi El; Indriani, Nurul; Sofya, Sri Winarni (Jurnal Multidisiplin Sahombu, 2025)
Cosmetics based on natural ingredients are increasingly favoured due to their perceived safety and environmental friendliness. One traditional plant with potential for development is water cress (Impatiens balsamina L.), which has long been utilised as a traditional medicine. This research aims to design a formulation and evaluate the preparation of cream nail polish with the additional component of water cress powder. This plant is known to contain flavonoids such as kaempferol and quercetin, which are beneficial for maintaining nail health. The study employed an experimental method with four formulations of nail polish, namely F0 (without powder), F1 (0.3%), F2 (0.5%), and F3 (0.75%). The preparation process involved the use of additional materials such as PVP, titanium dioxide, castor oil, methylparaben, and alcohol. Evaluation included organoleptic tests, homogeneity, pH, adhesion, spreadability, and hedonic testing involving 30 adolescent to adult panellists. The results indicated that all formulations exhibited good physical stability, pH values in accordance with standards, and high levels of preference, particularly for formulation F3 in terms of texture and final appearance. The addition of water cress seed powder provides additional benefits for nail moisture and protection. Thus, water cress seed powder can be considered as an alternative ingredient in the production of safer and more environmentally friendly cosmetic products. This research is expected to open new opportunities in the development of herbal-based cosmetics